Nautical Tourism, Carrying Capacity and Environmental Externality in the Lagoon of Marano and Grado - Francesco Silvestri; Stefano Ghinoi; Vincenzo Barone (Fondazione Eni Enrico Mattei (FEEM), 2013)
Tourism and environmental preservation are often conflicting activities, mainly in areas such as coastal lagoons, where seaside mass-tourism comes into contact with a very sensitive ecological system. In this paper we deal with a classical problem of both environmental and tourism economics, the internalization of environmental costs of tourism, focusing on the nautical fruition of the Lagoon of Marano and Grado (North-Eastern Italy, Friuli Venezia Giulia Region). Using different instruments, both theoretical (Carrying Capacity framework, Polluter-Payer principle, Coase compensation) and empirical (Cluster analysis, Log-log regression, Forecasting model, cost and benefit calculation through actual market values), we get the result that a standard Coasian equilibrium (unit external cost equal to unit private benefit) doesn't hold, and a higher coverage of the local berths endowment (i. e. a higher vessels transit in the Lagoon) is more effective for nature conservation than a tempered fruition. Another interesting result is that the best available solution to internalize environmental externality is a mixed one, comprehensive of a command and control rule (a speed-limit prescription), and a compensation scheme.
Keywords: Q01; Q26; Q57; 330; Tourism Carrying Capacity; Nature conservation; Externalities; Empirical studies